Financial transaction tax contributes to more sustainability in financial markets - Dorothea Schäfer (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
We argue that a financial transaction tax complements financial market regulation. With the tax, governments have an additional instrument at hand to influence trading activity. FTT aims to reduce regulatory arbitrage, flash trading, overactive portfolio management, excessive leverage and speculative transactions of financial institutions. The focus clearly addresses these classes of activities that have contributed to the financial crisis. However, if contrary to expectations harmful transactions will not be curbed, FFT generates at least large tax revenues that can contribute to cover the costs of the financial crisis. The trend towards centralized clearing and depositaries makes tax evasion more difficult than it was in the past. Tax avoidance is, of course, never completely avoidable. Therefore the effect of the tax should be monitored closely so that governments can react quickly if tax loopholes and taxinduced geographical relocation plans of financial institutions come to light.
Keywords: G20; G24; G28; 330; Financial stability; transaction tax; public good; central depository